2015
DOI: 10.1089/thy.2015.0058
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Nonradioactive Screening Method Identifies Genistein and Xanthohumol as Potent Inhibitors of Iodothyronine Deiodinases

Abstract: A rapid nonradioactive screening method based on the Sandell-Kolthoff reaction is suitable for identification of environmental, nutritive and pharmacological compounds modulating activities of human deiodinase enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 24 publications
0
42
0
1
Order By: Relevance
“…7). A more recent study examined compound effects on all three Dio isoforms individually and revealed xanthohumol as an inhibitor with micromolar potency on Dio1/2/3 (IC 50 1.5-3 mM), and genistein as a compound with similar potency (IC 50 3 mM), but specific for Dio1 (Renko et al 2015; Fig. 7).…”
Section: Propylthiouracil (Ptu)mentioning
confidence: 97%
“…7). A more recent study examined compound effects on all three Dio isoforms individually and revealed xanthohumol as an inhibitor with micromolar potency on Dio1/2/3 (IC 50 1.5-3 mM), and genistein as a compound with similar potency (IC 50 3 mM), but specific for Dio1 (Renko et al 2015; Fig. 7).…”
Section: Propylthiouracil (Ptu)mentioning
confidence: 97%
“…Supplementing the diet with IF was reported to triple the risk of overt hypothyroidism in patients with subclinical hypothyroidism [3]. Isoflavones may interact with various molecular targets of the thyroid hormone system: both genistein and daidzein can act as competitive substrates for thyroid peroxidase (TPO) [4,5]; genistein, and with a lower potency daidzein, inhibit binding of transthyretin (TTR) to thyroxin (T4) and triiodothyronine (T3) [6], while only genistein act as an inhibitor of type 1 deiodinase (Dio1) in vitro [7]. However, the goitrogenic potential of IF in vivo depends on numerous factors, including insufficient iodine in the diet or co-exposure with other goitrogen [8].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Besides TPO activity, discussed above, deiodination via 5DI can also be affected by baicalein, quercetin, kaempferol and rutin [69]. Xanthohumol FRTL-5 cells [89]; HEK293 cells [90] ↑IU [89]; iodothyronine deiodinases I [90] Effects listed in the right column and separated by semicolons have been derived from corresponding models shown in the middle column and separated by respective semicolons. 5DI, type I 5´-deiodinase; AC, anticancer; R, rat; ↑, increase; ↓, decrease; P, porcine; I , inhibit; G, goitrogenic; AT, antithyroid; HypoT, hypothyroidism; IU, iodide uptake; TH, thyroid hormone; M, mice; ATC, anaplastic thyroid carcinoma; FTC, follicular thyroid carcinoma; PTC, papillary thyroid carcinoma; MTC, medullary thyroid carcinoma.…”
Section: Effects Of Phenolic Compounds On Thyroidmentioning
confidence: 99%